A Sufficient Condition for a Unique Nonnegative Internal Rate of Return - Norstrom, Carl J. (Journal of Financial and Quantitative Analysis, 1972)
A proposition is proved which shows that each member of an important class of investment and financing projects has a unique nonnegative internal rate of return. Nonuniqueness of the internal rate of return is thus shown to occur less frequently than formerly believed. The correspondence between the proposition and previous results on the uniqueness of the internal rate of return is briefly indicated.